Combustion Noise - Schwarz, Anna; Janicka, Johannes (Springer Berlin Heidelberg : Imprint: Springer, 2009)
The reduction of noise emissions is a topic of increasing relevance in the public as well as for the economy. So far, the research has mainly concentrated on aerodynamic noise formation by airplanes, as well as other vehicles. The authors of this book go beyond this standard approach for noise reduction and explore the noise generation by combustion. They develop methods and design criteria in order to minimize the noise formation by combustion in general but in particular for aircraft engines in particular. Hereby the research is focused on the noise formation and propagation in the environment directly linked to the combustion process, since today the understanding of these detailed formation mechanisms of combustion noise is still fragmentary. The book gives a detailed insight into combustion noise and the underlying physical processes combining experiments and simulations.